Poorly differentiated thyroid carcinoma arising in struma ovarii- a report of two extremely rare cases - Yadav Subhash; Menon Santosh; Godkhindi Vishwapriya; Deodhar Kedar (Elsevier, 2020)
Struma ovarii is a specialized variant of ovarian teratoma represented by predominance (>50%) of thyroid tissue, and constitutes about 2.7% of all newly diagnosed ovarian teratomas. The histomorphological spectrum of the constituent thyroid tissue can range from normal banal thyroid follicles to adenoma like lesion to thyroid-type carcinomas. Malignancy arising in struma ovarii is very rare with most of the reported malignancies being the usual papillary thyroid carcinoma or follicular carcinoma. Poorly differentiated thyroid carcinoma (PDTC) arising in struma ovarii is extremely rare with only 9 cases reported in modern English literature Herein, we report two cases of PDTC in middle aged women, who presented with adnexal masses. The vagaries involved in establishing this diagnosis and discussion of differential diagnosis with value of immunohistochemistry is emphasized.